2014
DOI: 10.3109/01443615.2014.991291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postural changes on inferior vena cava dimensions and its influence on haemodynamics during caesarean section under spinal anaesthesia

Abstract: The effect of postural changes on inferior vena cava (IVC) dimensions and its influence on intra-operative haemodynamics in term parturients can be studied using abdominal ultrasound by a subcostal approach. Thirty-two term parturients scheduled to undergo elective caesarean section under spinal anaesthesia were recruited in this observational study. End expiratory diameter and collapsibility index of IVC was measured preoperatively in 3 different positions - supine, recumbent with wedge and left lateral posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The results of an observational study carried out in India with pregnant women submitted to spinal anesthesia for elective cesarean section corroborates with this fact. That study indicated arterial hypotension in 76% of pregnant women after spinal anesthesia and that the largest reductions, of 20% in systolic blood pressure, occurred between the sixth and seventh minutes after the anesthetic procedure [17].…”
Section: Discussionmentioning
confidence: 95%
“…The results of an observational study carried out in India with pregnant women submitted to spinal anesthesia for elective cesarean section corroborates with this fact. That study indicated arterial hypotension in 76% of pregnant women after spinal anesthesia and that the largest reductions, of 20% in systolic blood pressure, occurred between the sixth and seventh minutes after the anesthetic procedure [17].…”
Section: Discussionmentioning
confidence: 95%
“…However, few studies exist which define their role in predicting fluid responsiveness under SA thereby limiting the hypotension. [ 5 6 7 ] In our first case, assessment of volume status and preloading was done under USG guidance. However, bradycardia followed by cardiac arrest occurred intraoperatively under subarachnoid block, which could be due to unopposed vagal response and handling of huge ovarian cyst which might have resulted in IVC occlusion leading to relative hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available on the ultrasound assessment of inferior vena cava dimensions and collapsibility during inspiration and expiration in normal and complicated pregnancies. The diameter of the inferior vena cava changes significantly after intravenous volume load or changed maternal position in uncomplicated, term pregnancy. Compared with normal pregnancy, the vena cava collapsibility index, defined as ((Ø expiration – Ø inspiration)/Ø expiration) × 100% (where Ø is the diameter of the vena cava), is reduced in both late‐onset PE and PE with fetal growth restriction.…”
Section: Methods For Assessing Venous Hemodynamics and Plasma Volumementioning
confidence: 99%